2007
DOI: 10.1108/13527600710775739
|View full text |Cite
|
Sign up to set email alerts
|

Making a life or making a living?

Abstract: PurposeThe contemporary managerial work place is changing; baby boomers, the globalization and an increased participation of females in the workforce is redefining what value systems future managers’ will hold. This paper aims to build upon the traditional research on work ethics which focused primarily on working individuals. It seeks to explore future managers’ value systems on life vs work, in a cross‐national context.Design/methodology/approachPreviously validated questionnaires, containing 33 work–life va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(7 citation statements)
references
References 61 publications
0
4
0
Order By: Relevance
“… 57 Millennials favor flexible working conditions and value leisure and work-life balance; 64 they prefer “making a life” over “making a living”. 65 …”
Section: Theory and Hypothesesmentioning
confidence: 99%
“… 57 Millennials favor flexible working conditions and value leisure and work-life balance; 64 they prefer “making a life” over “making a living”. 65 …”
Section: Theory and Hypothesesmentioning
confidence: 99%
“…[17][18][19]. Interestingly, some studies have found that, specifically, millennials may value time over money, suggesting, among other things, a strong prevalence of hedonism and self-direction [81,90,91]. With regard to their readiness to join the workforce, some arguments have been made that the high moral and ethical values that have emerged in some studies make especially millennials very prepared to enter today's business environment [19,43], but their high expectations in terms of career advancement do not [17].…”
Section: Generations Y and Z And Their Personal Values In The Industry 40 Workplacementioning
confidence: 99%
“…Millennials are defined as people born after the 1980s (Warner and Zhu, 2018) and are also referred to as ‘Generation Y’ (Strauss and Howe, 1991). This new generation can be characterized by their date of birth, but more importantly, by the major evolutionary changes that have occurred during their lifetime, including rapid development of technology, globalization and changing social values, which encourage this generation to openly express their individualistic needs (Loughlin and Barling, 2001; Ng et al, 2010; Zhang et al, 2007).…”
Section: Introductionmentioning
confidence: 99%